Pengaruh Strategi Pemasaran terhadap Kinerja Perusahaan melalui Pemasaran Media Sosial - Ernita, Mahdar; Gunawan, Deni; Rangkuti, Hartati Zuraidah; Irawan, Hari; Lestari, Lisa (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2024)
The purpose of this study is to determine the influence of marketing strategies on company performance through social media in Indonesia today. By using literature research methods or collecting data from the internet and by using case studies from previous journals. The location of this study is Indonesia. Based on the results of research obtained from three previous studies, it was found that social media marketing has a great influence on company performance